High-repairing anisotropic conductive adhesive film and application thereof
By adding long-chain flexible monomers and silane coupling agents to the conductive film formulation, the problem of residue in anisotropic conductive films during the repair process was solved, achieving efficient separation and repair of the film from the glass substrate.
Patent Information
- Application Number
- CN202211724142.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2026-01-06
- Estimated Expiration
- 2042-12-30
AI Technical Summary
Existing anisotropic conductive films are prone to leaving residues on flexible COF or FPC during the repair process, leading to damage. Furthermore, existing photoradical methods cannot effectively improve the repairability of radical polymerization systems.
Adding long-chain flexible monomers and silane coupling agents to the conductive adhesive film formulation increases the interfacial adhesion to the glass substrate, allowing the adhesive film to remain on the glass substrate after peeling, facilitating repair.
It improves the adhesion at the peel interface between the adhesive film and the glass substrate, reduces the difficulty of repair, shortens the repair time, and enhances the strength of the adhesive film itself.
Smart Images

Figure BDA0004029024870000071
Abstract
Description
Technical Field
[0001] This invention belongs to the field of anisotropic conductive film technology, and relates to a highly repairable anisotropic conductive film and its applications. Background Technology
[0002] When bonding substrates and electronic components using anisotropic conductive film (ACF), poor conductivity can occur due to misalignment of the electronic components or inadequate curing of the ACF, requiring repair. Currently, the common repair method involves swelling the ACF with a specific solvent and then manually wiping it off with a cotton swab or brush. However, in existing repair processes, the ACF may remain within the flexible COF or FPC, easily causing damage.
[0003] Chinese patent application (publication number: CN101336278A) discloses adding a photoradical generator to an adhesive system formulation. After hot pressing and curing, the photoradical generator is irradiated with active energy rays to generate free radicals, causing the molecular chains of polymers in the cured product to be broken, making the cured product easily soluble or swellable in a specified solvent, thus facilitating repair treatment. However, this method is only applicable to epoxy resin curing systems. For ACF systems with free radical polymerization, after the free radical generator is irradiated with active energy rays, the free radicals will cause the ACF to react more strongly and have a higher curing modulus, failing to break the molecular chains of the polymers and therefore failing to achieve the purpose of improving repairability. Summary of the Invention
[0004] The purpose of this invention is to address the aforementioned problems in the prior art by proposing a highly repairable anisotropic conductive film with added long-chain flexible monomers and silane coupling agents, which allows the cured ACF to selectively remain on the glass substrate after peeling, facilitating repair.
[0005] The objective of this invention can be achieved through the following technical solutions:
[0006] A highly repairable anisotropic conductive adhesive film, wherein the raw materials of the highly repairable anisotropic conductive adhesive film, by weight, include: 5-15 parts long-chain flexible monomer, 0.1-4 parts silane coupling agent, 5-15 parts butyl rubber, 35-65 parts polyurethane-acrylate, 1-10 parts conductive particles, 10-30 parts silica, 1-10 parts titanium dioxide, 1-10 parts free radical initiator, and 0-20 parts other additives.
[0007] This invention adds long-chain flexible monomers and silane coupling agents to the anisotropic conductive adhesive film formulation system, causing the weak points of the bonding system to appear at the interface between ACF and COF or FPC. This allows the ACF to remain on the glass substrate after peeling, facilitating repair. The long-chain flexible monomers improve the strength of the anisotropic conductive adhesive bulk and reduce the crosslinking density, thus improving the repairability of the ACF; the silane coupling agent enhances the interfacial adhesion between the ACF and the glass substrate.
[0008] In this invention, long-chain rigid monomers of polyfunctional acrylates with saturated or unsaturated rings in the main chain cannot be added. This is because the addition of long-chain rigid monomers reduces the strength of the anisotropic conductive adhesive body, making it prone to breakage during peeling. As a result, the anisotropic conductive adhesive remains on the glass substrate, COF or FPC surface, which is difficult to handle.
[0009] Preferably, the ratio of the long-chain flexible monomer to the silane coupling agent is (1-10):1.
[0010] Preferably, the long-chain flexible monomer includes one or more of the following: multifunctional acrylate monomers with 8 or more carbon chains and methacrylate monomers.
[0011] Further preferably, the long-chain flexible monomer includes one or more of polyethylene glycol diacrylate, neopentyl hydroxypentanoate diacrylate, 1,9-nonanediol diacrylate, 1,10-decanediol diacrylate, and propoxyglycerol triacrylate.
[0012] More preferably, the long-chain flexible monomer is a compound of polyethylene glycol diacrylate and neopentyl glycol diacrylate in a mass ratio of 1:(0.5-2).
[0013] Preferably, the silane coupling agent includes one or more of vinylsilane, aminopropylsilane, glycidyl ether silane, methacryloxypropylsilane, mercaptopropylsilane, diethylaminosilane, anilinemethylsilane, dichloromethylsilane, phenyltrimethylsilane, and methyltriethylsilane.
[0014] Preferably, the free radical initiator includes one or more of alkyl peroxides, alkyl hydroperoxides, lipid peroxides, azobisisobutyronitrile, diacyl peroxide, and persulfates.
[0015] The present invention also discloses an application of a highly repairable anisotropic conductive film. The application process includes: placing the highly repairable anisotropic conductive film as an adhesive between a glass substrate and a COF or FPC. When peeling is required, the glass substrate and the COF or FPC are separated by setting a separation mechanism, and the highly repairable anisotropic conductive film remains on the glass substrate, which is then removed and repaired by acetone.
[0016] Preferably, the adhesion between the highly repairable anisotropic conductive film and the glass substrate can reach 893 gf / cm, and the time for acetone removal and repair can be as low as 30 seconds.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. This invention increases the adhesion at the peel interface between the anisotropic conductive film and the glass substrate by adding long-chain monomers and silane coupling agents to the formulation system, and allows the anisotropic conductive film to remain on the glass substrate after peeling, which facilitates repair.
[0019] 2. By leaving the cured anisotropic conductive film on the glass substrate, the present invention significantly reduces the difficulty of repair and shortens the repair time compared to leaving the anisotropic conductive film on COF or FPC.
[0020] 3. This invention adds long-chain flexible monomers to reduce crosslinking density and increase the strength of the anisotropic conductive film body. Detailed Implementation
[0021] The following are specific embodiments of the present invention, which further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0022] Example 1
[0023] The raw materials of the highly repairable anisotropic conductive film in this embodiment, by weight, include 9 parts of long-chain flexible monomers (4 parts of polyethylene glycol diacrylate, 5 parts of neopentyl glycol diacrylate hydroxypentanoate), 3 parts of silane coupling agent (methacryloyloxypropylsilane (CAS: 14513-34-9)), 10 parts of butyl rubber, 42 parts of polyurethane-acrylate, 3 parts of conductive particles, 15 parts of silica, 6 parts of titanium dioxide, and 5 parts of free radical initiator (azobisisobutyronitrile).
[0024] After mixing all the raw materials, they are coated and slit to form a highly repairable anisotropic conductive film with a thickness of 35μm.
[0025] A highly repairable anisotropic conductive film with dimensions of 30*2mm was used to bond a glass substrate and a COF, and its performance was tested. The specific results are shown in Table 1.
[0026] Example 2
[0027] The raw materials of the highly repairable anisotropic conductive film in this embodiment, by weight, include 9 parts long-chain flexible monomers (3 parts polyethylene glycol diacrylate, 6 parts neopentyl glycol diacrylate hydroxypentanoate), 3 parts silane coupling agent (methacryloyloxypropylsilane), 10 parts butyl rubber, 42 parts polyurethane-acrylate, 3 parts conductive particles, 15 parts silica, 6 parts titanium dioxide, and 5 parts free radical initiator (azobisisobutyronitrile).
[0028] After mixing all the raw materials, they are coated and slit to form a highly repairable anisotropic conductive film with a thickness of 35μm.
[0029] A highly repairable anisotropic conductive film with dimensions of 30*2mm was used to bond a glass substrate and an FPC, and its performance was tested. The specific results are shown in Table 1.
[0030] Example 3
[0031] The raw materials of the highly repairable anisotropic conductive film in this embodiment, by weight, include 9 parts of long-chain flexible monomer (polyethylene glycol diacrylate), 3 parts of silane coupling agent (methacryloyloxypropylsilane), 10 parts of butyl rubber, 42 parts of polyurethane-acrylate, 3 parts of conductive particles, 15 parts of silica, 6 parts of titanium dioxide, and 5 parts of free radical initiator (azobisisobutyronitrile).
[0032] After mixing all the raw materials, they are coated and slit to form a highly repairable anisotropic conductive film with a thickness of 35μm.
[0033] A highly repairable anisotropic conductive film with dimensions of 30*2mm was used to bond a glass substrate and a COF, and its performance was tested. The specific results are shown in Table 1.
[0034] Example 4
[0035] The raw materials for the highly repairable anisotropic conductive film in this embodiment, by weight, include 10 parts of long-chain flexible monomers (5 parts of polyethylene glycol diacrylate, 5 parts of neopentyl glycol diacrylate hydroxypentanoate), 2 parts of silane coupling agent (methacryloyloxypropylsilane), 10 parts of butyl rubber, 42 parts of polyurethane-acrylate, 3 parts of conductive particles, 15 parts of silica, 6 parts of titanium dioxide, and 5 parts of free radical initiator (azobisisobutyronitrile).
[0036] After mixing all the raw materials, they are coated and slit to form a highly repairable anisotropic conductive film with a thickness of 35μm.
[0037] A highly repairable anisotropic conductive film with dimensions of 30*2mm was used to bond a glass substrate and a COF, and its performance was tested. The specific results are shown in Table 1.
[0038] Example 5
[0039] The raw materials of the highly repairable anisotropic conductive film in this embodiment, by weight, include 11 parts of long-chain flexible monomers (5 parts of polyethylene glycol diacrylate, 6 parts of neopentyl glycol diacrylate hydroxypentanoate), 1 part of silane coupling agent (methacryloyloxypropylsilane), 10 parts of butyl rubber, 42 parts of polyurethane-acrylate, 3 parts of conductive particles, 15 parts of silica, 6 parts of titanium dioxide, and 5 parts of free radical initiator (azobisisobutyronitrile).
[0040] After mixing all the raw materials, they are coated and slit to form a highly repairable anisotropic conductive film with a thickness of 35μm.
[0041] A highly repairable anisotropic conductive film with dimensions of 30*2mm was used to bond a glass substrate and a COF, and its performance was tested. The specific results are shown in Table 1.
[0042] Example 6
[0043] The raw materials of the highly repairable anisotropic conductive film in this embodiment, by weight, include 7 parts long-chain flexible monomers (3 parts polyethylene glycol diacrylate, 4 parts neopentyl glycol diacrylate hydroxypentanoate), 5 parts silane coupling agent (methacryloyloxypropylsilane), 10 parts butyl rubber, 42 parts polyurethane-acrylate, 3 parts conductive particles, 15 parts silica, 6 parts titanium dioxide, and 5 parts free radical initiator (azobisisobutyronitrile).
[0044] After mixing all the raw materials, they are coated and slit to form a highly repairable anisotropic conductive film with a thickness of 35μm.
[0045] A highly repairable anisotropic conductive film with dimensions of 30*2mm was used to bond a glass substrate and a COF, and its performance was tested. The specific results are shown in Table 1.
[0046] Comparative Example 1
[0047] The raw materials of the highly repairable anisotropic conductive film in this comparative example, by weight, include 12 parts long-chain monomers (6 parts polyethylene glycol diacrylate, 6 parts neopentyl glycol diacrylate hydroxypentanoate), 10 parts butyl rubber, 42 parts polyurethane-acrylate, 3 parts conductive particles, 15 parts silica, 6 parts titanium dioxide, and 5 parts free radical initiator (azobisisobutyronitrile).
[0048] After mixing all the raw materials, they are coated and slit to form an anisotropic conductive film with a thickness of 35μm.
[0049] An anisotropic conductive film with dimensions of 30*2mm was used to bond a glass substrate and a COF, and its performance was tested. The specific results are shown in Table 1.
[0050] Comparative Example 2
[0051] The raw materials of the highly repairable anisotropic conductive film in this comparative example, by weight, include 12 parts of long-chain monomer (tricyclodecanedimethyl diacrylate), 10 parts of butyl rubber, 42 parts of polyurethane-acrylate, 3 parts of conductive particles, 15 parts of silica, 6 parts of titanium dioxide, and 5 parts of free radical initiator (azobisisobutyronitrile).
[0052] After mixing all the raw materials, they are coated and slit to form an anisotropic conductive film with a thickness of 35μm.
[0053] An anisotropic conductive film with dimensions of 30*2mm was used to bond a glass substrate and a COF, and its performance was tested. The specific results are shown in Table 1.
[0054] Comparative Example 3
[0055] The raw materials for the highly restorative anisotropic conductive film in this comparative example, by weight, include 9 parts long-chain monomers (3 parts polyethylene glycol diacrylate, 3 parts neopentyl glycol hydroxypentanoate diacrylate, 3 parts tricyclodecane dimethyl diacrylate), 3 parts silane coupling agent (methacryloyloxypropylsilane), 10 parts butyl rubber, 42 parts polyurethane-acrylate, 3 parts conductive particles, 15 parts silica, 6 parts titanium dioxide, and 5 parts free radical initiator (azobisisobutyronitrile).
[0056] After mixing all the raw materials, they are coated and slit to form a highly repairable anisotropic conductive film with a thickness of 35μm.
[0057] A highly repairable anisotropic conductive film with dimensions of 30*2mm was used to bond a glass substrate and a COF, and its performance was tested. The specific results are shown in Table 1.
[0058] Comparative Example 4
[0059] The raw materials of the highly repairable anisotropic conductive film in this comparative example, by weight, include 9 parts of long-chain rigid monomer (tricyclodecanedimethyl diacrylate), 3 parts of silane coupling agent (methacryloyloxypropylsilane), 10 parts of butyl rubber, 42 parts of polyurethane-acrylate, 3 parts of conductive particles, 15 parts of silica, 6 parts of titanium dioxide, and 5 parts of free radical initiator (azobisisobutyronitrile).
[0060] After mixing all the raw materials, they are coated and slit to form a highly repairable anisotropic conductive film with a thickness of 35μm.
[0061] A highly repairable anisotropic conductive film with dimensions of 30*2mm was used to bond a glass substrate and a COF, and its performance was tested. The specific results are shown in Table 1.
[0062] Table 1. Data on the Amount and Performance of Some Raw Materials Added
[0063]
[0064] As shown in Table 1, the formulation system of the present invention, as shown in Examples 1-4, produces ACF with good adhesion at the peel interface with the glass substrate, and the repair time using acetone is also shorter. In Example 4, the amount of silane coupling agent added is slightly less than that in Example 1, but due to the increase in long-chain flexible monomers and the decrease in crosslinking density, the repair time is further shortened. In Example 5, due to the larger ratio of long-chain flexible monomers to silane coupling agent, the adhesion at the peel interface between ACF and the glass substrate becomes worse, and ACF remains on COF, increasing the difficulty of repair. In Example 6, the amount of silane coupling agent added is larger, which increases the adhesion at the peel interface between ACF and the glass substrate, but the repair time is slightly increased.
[0065] In Comparative Example 1, the absence of a silane coupling agent caused the ACF to remain on the COF, increasing the difficulty of repair. In Examples 2-4, the presence of long-chain rigid monomers reduced the bulk performance of the ACF, causing it to break during peeling and making repair even more difficult.
[0066] In summary, this invention increases the adhesion of the anisotropic conductive film to the glass substrate by adding long-chain flexible monomers and silane coupling agents to the formulation system, so that the anisotropic conductive film remains on the glass substrate after peeling, facilitating repair.
[0067] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to substitute them, without departing from the spirit of the invention or exceeding the scope defined by the appended claims.
Claims
1. A highly repairable anisotropic conductive adhesive film, characterized by, The high-repairing anisotropic conductive adhesive film comprises, by weight fraction, 5-15 parts of long-chain flexible monomer, 0.1-4 parts of silane coupling agent, 5-15 parts of butyl rubber, 35-65 parts of polyurethane-acrylate, 1-10 parts of conductive particles, 10-30 parts of silicon dioxide, 1-10 parts of titanium dioxide, 1-10 parts of free radical initiator, and 0-20 parts of other auxiliary agents; and does not contain long-chain rigid monomer with a main chain having a saturated or unsaturated ring and a multi-functional acrylate. The long-chain flexible monomer and the silane coupling agent are added in a ratio of (1-10):
1. The long-chain flexible monomer comprises one or more of polyethylene glycol diacrylate, hydroxypivalic acid neopentyl glycol diacrylate, 1,9-nonanediol diacrylate, and 1,10-decanediol diacrylate. The silane coupling agent is 3-methacryloyloxypropylmethyldimethoxysilane with a CAS number of 14513-34-9.
2. The high-reliability anisotropic conductive film according to claim 1, wherein The long-chain flexible monomer is a mixture of polyethylene glycol diacrylate and hydroxypivalic acid neopentyl glycol diacrylate in a mass ratio of 1:(0.5-2).
3. Use of the high-repairing anisotropic conductive adhesive film according to claim 1, characterized in that, The application process comprises: placing the high-repairing anisotropic conductive adhesive film as an adhesive between a glass substrate and a COF or FPC; when peeling is required, separating the glass substrate from the COF or FPC, leaving the high-repairing anisotropic conductive adhesive film on the glass substrate, removing and repairing by acetone.
4. Use according to claim 3, characterized in that, The adhesion between the high-repairing anisotropic conductive adhesive film and the glass substrate can reach 893 gf / cm, and the time for removal and repair by acetone can be as low as 30 s.
Citation Information
Patent Citations
Heat curable adhesive
CN101336278A
Photo-thermal dual curable type anisotropic conductive resin and conductive film as well as preparation method of conductive resin and conductive film
CN102634286A
Low-modulus acrylate conductive adhesive used in semiconductor chip packaging, and preparation method thereof
CN103320022A
Low-Tg (low-glass-transition-temperature) and low-silver-content conducting resin for photovoltaic imbrication component
CN109439268A
Anisotropic conductive adhesive film capable of being stored and transported at normal temperature and attaching method thereof
CN115449305A